2009
DOI: 10.1080/17450390903052698
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the source of nitrogen supplementation on nitrogen balance, rates of plasma leucine turnover, protein synthesis and degradation in sheep

Abstract: Combined experiments of the isotope dilution method of [1-(13)C]leucine, open-circuit calorimetry and nitrogen (N) balance test were used to determine the effect of the source of N supplementation on N balance, whole body protein synthesis (WBPS) and degradation (WBPD) in sheep. The experiment was performed in a replicated 3 × 3 Latin square design. The control diet consisted of timothy hay, ground maize and soybean meal. The urea diet was the control diet supplemented with 1.5% urea. The SBM diet contained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 32 publications
7
15
0
Order By: Relevance
“…Plasma α-KIC enrichments were used for calculation of LeuTR as described previously (Sano et al 2009). Whole-body protein synthesis (WBPS) was calculated from the equation as described by Schroeder et al (2006).…”
Section: Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma α-KIC enrichments were used for calculation of LeuTR as described previously (Sano et al 2009). Whole-body protein synthesis (WBPS) was calculated from the equation as described by Schroeder et al (2006).…”
Section: Calculationsmentioning
confidence: 99%
“…Concentrations of plasma NEFA were enzymatically determined using the diagnostic kit (NEFA C test, Wako, Japan). Concentrations of VFA in the rumen fluid were determined with gas chromatography (HP-5890, Hewlett Packard, USA) after steam distillation, as described previously (Sano et al 2009). Ammonia concentrations in rumen fluid were determined by a colorimetric method (Weatherburn 1967).…”
mentioning
confidence: 99%
“…Plasma LeuTR, LeuOX and WBPS were calculated as described previously (Sano et al 2009 where E CO 2 is the isotope enrichment of exhaled 13 CO 2 and V CO 2 is the CO 2 production rate. Recovery fraction of the exhaled CO 2 production in the animal body was estimated to be 0.81 as described by Allsop et al (1978).…”
Section: Calculationsmentioning
confidence: 99%
“…However, little information is available focusing on the effect of N supplementation on whole body kinetics of amino acid and protein metabolism using an isotope dilution method. Sano et al (2009) reported that in sheep fed roughage-based diets, whole body protein synthesis (WBPS) and degradation, using the [1- 13 C]leucine (Leu) technique, remained unchanged with supplementation of urea and SBM. On the contrary, availability of soluble carbohydrates influenced microbial protein synthesis in the rumen of cattle (Rooke and Armstrong 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation